Enhancing energy efficiency with poncebloc and hemp wool: a Moroccan case study - Yasser Boukioud; Kaoutar Senhaji Rhazi; Youssef Mejdoub (Institute of Advanced Engineering and Science, 2024)
In recent years, the building sector's energy consumption in Morocco has been steadily increasing, highlighting the urgent need for sustainable building practices. Optimizing building parameters and the development of new insulation materials have become critical areas of research due to the significant energy losses associated with traditional insulation materials. Insulation materials can be a simple and cost-effective way to improve building energy efficiency and reduce environmental impact. Unfortunately, not all of these materials exhibit favorable thermal characteristics such as conductivity or heat capacity. Some involve complex production processes, while others are prohibitively expensive or toxic. At this juncture, the strategy of integrating ecological materials with insulation materials to enhance thermal performance holds considerable promise. This paper investigates the impact of the integration of poncebloc and hemp wool in inside temperature and annual consumption of a building construction numerically under a transient simulation program (TRNSYS). The results show that by using these two materials along with double-glazed windows, energy savings ranging from 50-55% can be achieved.